Hypothetical Scenario between Sirius Corporation vs Magma Logistics based on Singapore and Japan Perspective - Mahmuddin; Hilbertus Sumplisius M. Wau (Talenta Publisher, Universitas Sumatera Utara, 2023)
Merger and Acquisition (M&A) is still one of key point in international business law. More and more Asian companies doing the transaction to thrive their business. In essence, M&A is a way of transfer of ownership and control in a business or more corporations. Sirius Corporation and Magma Logistic are two main parties in these issues. We will be conducting research and collect information regarding the hypothetical scenario and conclude the findings. There are several important things need to be highlighted such us jurisdiction, legal rights, and corporation strategies in the event of the transactions. Not only that, but timeline for this transaction also play a pivotal point when the M&A deal occur. A series of details event also included in the timeline in order to gain a deep understanding how the companies interact before the M&A occurs. We also compare how Singapore and Japan law and regulation difference with each other in term of M&A deals for Sirius Corporation and Magma Logistic. I believe these two jurisdictions are the most used for companies in Asian. The main reason because they have strict implementation and practical for business to use not like many others Asian countries.